2020
DOI: 10.33785/ijds.2020.v73i02.010
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of milk production in peri-urban dairy farms of Odisha

Abstract: East and South-eastern coastal plain zone of Odisha was purposively selected for conducting study. After complete enumeration, farms were categorized into small, medium and large categories on the basis of milch animals using cumulative square root frequency method. A total of 120 peri-urban dairy farms were selected from two towns namely Bhubaneswar town (Khorda district) and Cuttack town (Cuttack district). Budgeting technique was used to estimate costs and returns. Capital recovery cost method was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
4
3
1
Order By: Relevance
“…The share of total fixed cost and total variable cost to the overall gross maintenance cost was found to be 15.36 per cent and 84.64 per cent, respectively. The result obtained was in conformity with earlier studies conducted by Vanishree et al (2018), Athare et al (2019) and Acharya and Malhotra (2020). The contribution of overall feed and fodder cost to the gross cost was found to be 70.71 per cent, followed by overall labour cost (9.68%).…”
Section: Costs and Returns Of Milk Production Of Buffalossupporting
confidence: 92%
See 2 more Smart Citations
“…The share of total fixed cost and total variable cost to the overall gross maintenance cost was found to be 15.36 per cent and 84.64 per cent, respectively. The result obtained was in conformity with earlier studies conducted by Vanishree et al (2018), Athare et al (2019) and Acharya and Malhotra (2020). The contribution of overall feed and fodder cost to the gross cost was found to be 70.71 per cent, followed by overall labour cost (9.68%).…”
Section: Costs and Returns Of Milk Production Of Buffalossupporting
confidence: 92%
“…Hence, lowest cost of milk production per litre of milk was estimated in case of largeherd size and highest in case of smallherd size category due to the economics of scale in dairying. The result regarding the per litre cost of milk production was in accordance with earlier studies conducted by Lal and Chandel (2016) and Acharya and Malhotra (2020).…”
Section: Costs and Returns Of Milk Production From Crossbred Cowssupporting
confidence: 90%
See 1 more Smart Citation
“…With the current trend in the country India will be able to produce about 217 MT of milk by 2025. There is an ample room for promotion, production and distribution of liquid milk and its products, which policy makers and dairy industry can use it in their favour [6]. The dairy sector provides employment opportunities directly or indirectly to 15 million people in India [7].…”
Section: Original Research Articlementioning
confidence: 99%
“…Milk productivity and returns per liter of milk of crossbred cows were more than buffalo. Therefore, it can be concluded that rearing of a crossbred cow would economically benefit the farmers (Acharya and Malhotra, 2020). The main player in the milk value chain of Odisha consists of both formal and informal sectors.…”
Section: Milk Production Scenario In Odishamentioning
confidence: 99%